2016
DOI: 10.1007/s00204-016-1804-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and chronic diseases: the current state of the art

Abstract: The objective was to provide the current state of the art regarding the role of vitamin D in chronic diseases (osteoporosis, cancer, cardiovascular diseases, dementia, autism, type 1 and type 2 diabetes mellitus, male and female fertility). The document was drawn up by panelists that provided their contribution according to their own scientific expertise. Each scientific expert supplied a first draft manuscript on a specific aspect of the document's topic that was subjected to voting by all experts as "yes" (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 79 publications
0
84
0
6
Order By: Relevance
“…The wide pleiotropism of this natural hormone vitamin, which can be considered similar to other diet-derived plant polyphenols, antioxidants, and additional nutritional supplements, 1 is disconcerting, compared with the high frequency of deficient levels of circulating vitamin D in the human population. [2][3][4][5] Despite its importance, people seem to live perfectly with apparently long-lasting deficiencies of vitamin D. Vitamin D is an ancient hormonal molecule; it is photosynthesized in all forms of life, starting from the phytoplankton ( 750 million years ago) to mammals and humans. 6 For certain aspects, vitamin D might be selected as one of the first natural antioxidant prohormones from nonplant-derived foods, and thus cells were instructed to synthesize it.…”
Section: Introductionmentioning
confidence: 99%
“…The wide pleiotropism of this natural hormone vitamin, which can be considered similar to other diet-derived plant polyphenols, antioxidants, and additional nutritional supplements, 1 is disconcerting, compared with the high frequency of deficient levels of circulating vitamin D in the human population. [2][3][4][5] Despite its importance, people seem to live perfectly with apparently long-lasting deficiencies of vitamin D. Vitamin D is an ancient hormonal molecule; it is photosynthesized in all forms of life, starting from the phytoplankton ( 750 million years ago) to mammals and humans. 6 For certain aspects, vitamin D might be selected as one of the first natural antioxidant prohormones from nonplant-derived foods, and thus cells were instructed to synthesize it.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of adequate 25-hydroxy vitamin D (25OHD) levels in the blood is required since it is essential for a large number of physiologic mechanisms beyond the classic actions in calcium homeostasis. The new role of vitamin D as a pro-hormone is rather focusing on other areas and it is also widening range of therapeutic applications in prevention and maintenance of endocrine health [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade the daily dosing targets have been elevated from 600 IU/d to 1500-2000 IU/d and considered blood 25OHD concentration as a clinically important surrogate outcome that correlates with health and disease [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, accumulating evidence has also demonstrated that the bone is an endocrine regulator of energy metabolism. For example, osteocalcin hormone secreted by the osteoblasts is a key regulator of glucose and fat metabolism [14, 15]. Despite the interrelationship between bone metabolism and the risk of diabetes, few studies have been conducted to identify the biomarkers of bone metabolism that may be associated with DR or DME.…”
Section: Discussionmentioning
confidence: 99%